Corruption KPK Threatened to Not Be Captured Board Of Directors of State-Owned Enterprises - A. Junaedi Karso (International Journal of Sociology and Law, 2025)
The Law on State-Owned Enterprises (BUMN) by the Indonesian House of Representatives on February 4, 2025 has been ratified, and then signed by President Prabowo Subianto on February 24, 2025, destroying the concept of who the state administrators are as regulated in Law Number 28 of 1999 concerning the Implementation of a Clean State Free from Corruption, Collusion, and Nepotism.Law No. 1 of 2025 concerning BUMN, places the directors, commissioners, and supervisors of the state-owned company not as state administrators. This means that the Corruption Eradication Commission or KPK can no longer handle law enforcement in BUMN if corruption occurs, except for the Police, Prosecutor's Office and BPK (supervision), as stated in Article 3X of Law No. 1 of 2025, which states that: "The Agency's organs and employees are not state administrators. It is emphasized again in Article 9G: Members of the Board of Directors, Board of Commissioners, and Supervisory Board of BUMN are not state administrators". Meanwhile, financial supervision is still carried out by the Audit Board as stated in Article 3K: Audit of the management and financial responsibility of the Agency is carried out by the Audit Board. Although in the KPK Law, it is stated in Article 11 paragraph (1) that: "In carrying out the duties as referred to in Article 6 letter e, the Corruption Eradication Commission has the authority to conduct investigations, inquiries, and prosecutions against Corruption Crimes that: a. involve law enforcement officers, State Administrators, and other people related to Corruption Crimes committed by law enforcement officers or State Administrators; and/or b. involve state losses of at least IDR 1,000,000,000.00 (one billion rupiah)".Therefore, the Law Order, the KPK must submit and obey to carry it out, because the Law (UU) functions as a basic or principal rule for organizing the state, regulating society, a tool to limit power, and as a means of social renewal. The Law also functions to regulate life in society, the nation, and the state and is expected to be able to resolve various problems that exist in society.In fact, the impact of corruption in BUMN is no joke. The destruction of economic growth, state and community income can be disrupted which results in direct state losses, but leads to the potential for increasing poverty and the loss of the government's safety net in the form of declining quality of public services and investor confidence in Indonesia, etc.